2006
DOI: 10.1111/j.1600-0838.2006.00589.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a simulated sprint competition in classical cross country skiing

Abstract: The objectives of this project were first to analyze the physiological response of a classical cross country (XC) skiing sprint competition, second, to examine the relationships of kinematic and physiological variables with sprint performance and third, to test the hypothesis that maximal speed in double poling (DP) and diagonal stride (DIAG) predicts sprint performance. Twelve elite skiers performed a treadmill-based simulation of a sprint competition that included two maximal speed tests (DP, DIAG), a test a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
116
1
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(136 citation statements)
references
References 35 publications
15
116
1
4
Order By: Relevance
“…For data collection, a slope of 2 deg and a speed of 14 km h −1 were selected as a good compromise to perform either the techniques used for high slope and slow speed, and those used mainly for flat and high speed skiing. The slope was in line with that selected for roller skiing investigations by other researchers (Mittelstadt et al, 1995;Sandbakk et al, 2012;Holmberg et al, 2005;Lindinger et al, 2009b;Stöggl et al, 2007;Vähäsöyrinki et al, 2008). The order of the techniques was randomized for each subject.…”
Section: Methodsmentioning
confidence: 63%
“…For data collection, a slope of 2 deg and a speed of 14 km h −1 were selected as a good compromise to perform either the techniques used for high slope and slow speed, and those used mainly for flat and high speed skiing. The slope was in line with that selected for roller skiing investigations by other researchers (Mittelstadt et al, 1995;Sandbakk et al, 2012;Holmberg et al, 2005;Lindinger et al, 2009b;Stöggl et al, 2007;Vähäsöyrinki et al, 2008). The order of the techniques was randomized for each subject.…”
Section: Methodsmentioning
confidence: 63%
“…Another study reported that the resting concentration of BDNF was not infl uenced by strength training in young subjects [14] . Maximal speed and strength are known to be important determinants of sprint performance [22,23] . Concentric and eccentric muscle strength are correlated with sprint performance because they refl ect sprinting in both the duration and the application of force.…”
Section: Discussionmentioning
confidence: 99%
“…Stoggl et al (2006Stoggl et al ( , 2007a and Holmberg and Nilsson (2008) have used double pole time trials in their research, and Stoggl et al (2007b) used a 1,100-m classic sprint; however, the relationship of UBP to a longer classical ski race involving a mix of diVerent classic techniques has not yet been investigated. Thus, the purpose of the present study was to evaluate the relationship between both short (·60 s) and long duration (4-12 min) laboratory-based UBP tests and average speed from a single mass start 10 km classical ski race.…”
Section: Introductionmentioning
confidence: 97%